Comments on non-Abelian T-duals and their holographic description - PAUL MERRIKIN (Physics Letters B, 2022)
We present three different Type IIB AdS4 Supergravity solutions, derived using the electrostatic-likeproblem formalism which preserves 8 Poincaré Supercharges. Two of these solutions correspond to the Abelian and non-Abelian T-duals of a Type IIA background, obtained from the dimensional reduction of 11D AdS4 × S7 Supergravity. The third solution is a new background with some special properties. We compute the Page charges in each case, and provide brane set-up descriptions of the geometries. Also, we argue that the non-Abelian T-dual can be understood as a zoom-in of a more general background with a well defined holographic dual.